Effectiveness of inflation targeting based monetary policy - Ahmed Rashid Almuain, Saad Salih Issa, Hameed Hasan Khalaf,; Ries Ahmed, Essia (Opción, 2019)
In this research, the performance of inflation targeting strategy was analyzed using the ordinary least square method (OLS) with the regression model for economic circumstances in Britain. The results of this investigation concluded that net lending ratio and total debt to GDP ratios have a positive and strong relationship with the inflation rate. It is concluded that the implementation of the inflation targeting policy has an impact on the economic performance in Britain. However, a proper monitoring and investigation of the current economic state are necessary before implementing inflation targeting policy.